The Delphi technique : a case study of its application in school administration : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts at Massey University - Lee, Foong Ngor Heidi (Massey University, 1985)
The objectives of this study were: 1) To ascertain the challenges facing school administrators during the remainder of this decade, using the Delphi Technique. 2) To evaluate the potential of the Delphi Technique for school administrators. To fulfil these objectives a small sample of school administrators (N=33) completed a three-round Delphi procedure. In the first round, participants were invited to respond to the question: "What are the challenges facing school administrators during the remainder of this decade?" A total of 136 statements were received and, after screening and editing, these were refined to a list of 34 items. For Round Two, respondents had their own Round One responses and the summary list of 34 items returned, and they were asked to reconsider the question about the future challenges facing school administrators, in the light of their previous reply and the group summary. A list of 42 statements, 33 of which appeared in the second round, was derived as a result of Round Two. In the final round, respondents were fed back the list of 42 statements and were asked to indicate the importance of each. A statistical analysis of data derived from Round Three indicated 'Staffing Practices and Issues' items were the most prominent amongst challenges facing school administrators during the remainder of this decade, with the most important issue being to 'improve staff professional competency and development through training, closer supervision and collegial support'. A Follow-Up Evaluation of this three-round Delphi project was carried out to obtain information relevant to the second objective outlined above. The sample of school administrators was sent a questionnaire which, inter alia, sought their opinions on: the degree to which they concurred with the outcomes from Round Three; difficulties they encountered during the project; and advantages and disadvantages of Delphi. The tenor of the respondents' comments in this Follow-Up Evaluation indicated general support for the Delphi Technique as a potentially viable tool for school administrators. And, finally, after considering the significant methodological issues that arose during the course of this study (e.g. the selection of the sample; the editing process) it was concluded that school administrators may find a number of advantages in using the Delphi Technique, particularly in areas such as curriculum planning, developing goals and objectives, and arriving at consensus and budgeting allocations.
Keywords: Delphi Technique; Decision-making; School administration; School administrators